Analytical Eigenstate Equivalent Circuit for Narrow-Slot Bi-Periodic Scatterers - Hernández-Escobar, Alberto; Mesa, Francisco; Esteban, Jaime; Abdo-Sánchez, María Elena; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (My University, 2023)
The analytical values of the parameters of an eigenstate-based equivalent circuit are obtained for the analysis and modeling of a simple bi-periodic scatterer. The scatterer geometry consists of a rotated, very narrow slot. Analytical values of this kind of equivalent circuit are obtained for the first time by comparison with a fully-analytical multi-mode equivalent circuit. Analytical results are contrasted with simulated ones, and a very good agreement is found.
Keywords: Antenas - Diseño y construcción; Circuitos electrónicos - Diseño; Electromagnetismo